Answer:
f( - 2) = 23
Step-by-step explanation:
![f(x) = 3 {x}^{2} - 2x + 7 \\ plug \: x = - 2 \\ f( - 2) = 3 {( - 2)}^{2} - 2( - 2)+ 7 \\ = 3 \times 4 + 4 + 7 \\ = 12 + 11 \\ \huge \red{ \boxed{ f( - 2) = 23}}](https://tex.z-dn.net/?f=f%28x%29%20%3D%203%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%2B%207%20%5C%5C%20plug%20%5C%3A%20x%20%3D%20%20-%202%20%5C%5C%20f%28%20-%202%29%20%3D%203%20%7B%28%20-%202%29%7D%5E%7B2%7D%20%20-%202%28%20-%202%29%2B%207%20%5C%5C%20%20%3D%203%20%5Ctimes%204%20%2B%204%20%2B%207%20%5C%5C%20%20%3D%2012%20%2B%2011%20%5C%5C%20%20%5Chuge%20%5Cred%7B%20%5Cboxed%7B%20f%28%20-%202%29%20%3D%2023%7D%7D)
3600 seconds.
60 minutes are in a degree
60 seconds are in a minute
If you multiply those you get 3600 seconds
Answer:
All that you would have to do is add 10 more blocks to show that its 10 more than 43
Answer:
I'm sorry I don't know the first one but the second one is (-3x^2b^3)^3
Step-by-step explanation: